ANALISIS HAMBATAN GREEN ROAD CONSTRUCTION STUDI KASUS : PROYEK PEMBANGUNAN KANTILEVER JALAN NASIONAL PARAPAT - AJIBATA - Asri Afriliany Surbakti; Mei Brilian Harefa (Universitas Quality, 2021)
Construction industry is one of the industries that has contributed the largest consumption of energy, water, natural resources, and waste generation, which cause environmental harm. Road construction is one of the construction industries that grow continuously, which can affect directly to the degradation of the environment. Green road construction is a sustainability action which is expected to minimize environmental damage due to construction projects as it can save natural resources, water and energy. Ministerial Regulation PUPR No. 5/2015 concerning General Guidelines for the Implementation of Sustainable Construction in the Implementation of Infrastructure in the Public Works and Settlements Sector, therefore the green road construction concept should have been implemented by contractors. The object of this study was National Road Cantilever Construction Project Parapat – Ajibata, Simalungun Regency, This study aims to investigate the application of green road construction concept, constraints that encountered by contractors on the green construction concept application, and solutions for contractors. This study used a descriptive percentage method to determine the magnitude of the green road construction concept application and a qualitative descriptive method to determine the constraints and solutions. The results of this study indicate that the green road construction concept was applied with a value of 3.3 or 65.45%. Constraints that encountered in the green road construction concept application was the lack of regulation from local government to oblige green road construction concept in all construction activities and contractor needed to spend a higher cost if they initiative to implement this concept. Researcher suggest several solutions include: the issuance of regulations regarding environmentally friendly construction by local government and awareness from contractors regarding the importance of environmentally friendly implementation.